Experimental study of the inhibition effect of CXCL12/CXCR4 in malignant pleural mesothelioma. (26th October 2018) - Li, Jianshuang; Li, Tong; Li, Shuo; Xie, Lipeng; Yang, Yi-Lin; Lin, Qiang; Kadoch, Orli; Li, Hui; Hou, Shengcai; Xu, Zhidong
Abstract : Previous studies have demonstrated that CXCL12/CXCR4 axis is closely related to tumors such as malignant pleural mesothelioma (MPM). This research was conducted in order to detect whether CXCL12/CXCR4 inhibitors could restrain MPM and have a synergistic effect with chemotherapy, also to investigate the relationship of CXCL12/CXCR4 with other gene expressions in MPM. Forty mice were injected MPM cells and randomly divided into four groups: the PBS (control group), AMD3100 (CXCR4-CXCL12 antagonist), pemetrexed and AMD3100 plus pemetrexed. The mice were treated respectively for duration of 3 weeks. The size, bioluminescence and weight of tumors were measured. The differences between gene expressions in each group were analyzed. The tumor weights of each treatment group were lower than that of the control group (p<0.05). The bioluminescence of the tumor of the AMD3100 treatment group and the AMD3100 plus pemetrexed treatment group were lower than that of the control group (p<0.05), and AMD3100 was shown to have synergistic effects with pemetrexed (p<0.05). Among the 2.5 billion genes, several hundreds of genes expressed differently between groups. Results show that AMD3100 and pemetrexed can inhibit the growth of MPM in vivo, also that there is a better result if both are used together. Our findings suggest that CXCL12/CXCR4 axis affects a certain amount of gene expression in MPM.